A Canonical EF‐Loop Directs Ca2+‐Sensitivity in Phospholipase C‐η2. Issue 3 (March 2014) - Popovics, Petra; Lu, Jin; Nadia Kamil, L.; Morgan, Kevin; Millar, Robert P.; Schmid, Ralf; Blindauer, Claudia A.; Stewart, Alan J.
ABSTRACT Phospholipase C‐η (PLCη) enzymes are a class of phosphatidylinositol 4, 5‐bisphosphate‐hydrolyzing enzymes involved in intracellular signaling. PLCη2 can sense Ca2+ (stimulated by ∼1 µM free Ca2+) suggesting that it can amplify transient Ca2+ signals. PLCη enzymes possess an EF‐hand domain composed of two EF‐loops; a canonical 12‐residue loop (EF‐loop 1) and a non‐canonical 13‐residue loop (EF‐loop 2). Ca2+‐binding to synthetic peptides corresponding to EF‐loops 1 and 2 of PLCη2 and EF‐loop 1 of calmodulin (as a control) was examined by 2D‐[1H, 1H] TOCSY NMR. Both PLCη2 EF‐loop peptides bound Ca2+ in a similar manner to that of the canonical calmodulin EF‐loop 1, particularly at their N‐terminus. A molecular model of the PLCη2 EF‐hand domain, constructed based upon the structure of calmodulin, suggested both EF‐loops may participate in Ca2+‐binding. To determine whether the EF‐hand is responsible for Ca2+‐sensing, inositol phosphate accumulation was measured in COS7 cells transiently expressing wild‐type or mutant PLCη2 proteins. Addition of 70 µM monensin (a Na+/H+ antiporter that increases intracellular Ca2+) induced a 4‐ to 7‐fold increase in wild‐type PLCη2 activity. In permeabilized cells, PLCη2 exhibited a ∼4‐fold increase in activity in the presence of 1 µM free Ca2+. The D256A (EF‐loop1) mutant exhibited a ∼10‐fold reduction in Ca2+‐sensitivity and was not activated by monensin, highlighting the involvement of EF‐loop 1 in Ca2+‐sensing. Involvement of EF‐loop 2 was examined using D292A, H296A, Q297A, and E304A mutants. Interestingly, the monensin responses and Ca2+‐sensitivities were largely unaffected by the mutations, indicating that the non‐canonical EF‐loop 2 is not involved in Ca2+‐sensing. J. Cell. Biochem. 115: 557–565, 2014. © 2013 Wiley Periodicals, Inc.